2020
DOI: 10.46781/al-mutharahah.v17i2.153
|View full text |Cite
|
Sign up to set email alerts
|

Kreativitas Siswa Dalam Penggunaan Gadget Pada Pembelajaran PAI Di Masa Covid-19

Abstract: The use of gadgets in addition to communication can also be used to support the learning process. The learning process during covid 19 takes place online. One of the media used for the continuity of the online learning process is gadgets. Learning during the Covid 19 pandemic requires student creativity in the learning process. Problems in the field have been used by students to access social media and play online games. The formulation of the problem in the study wanted to see how the creativity of students u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Mauladina and Giantara [33] through the results of interviews found that gadgets do have a negative effect because in addition to helping make the process online learning runs students also access media social media and playing online games. However, gadgets are also capable of creating students' creativity to create something that previously didn't exist and was not done by someone even though the results were not perfect.…”
Section: Resultsmentioning
confidence: 99%
“…Mauladina and Giantara [33] through the results of interviews found that gadgets do have a negative effect because in addition to helping make the process online learning runs students also access media social media and playing online games. However, gadgets are also capable of creating students' creativity to create something that previously didn't exist and was not done by someone even though the results were not perfect.…”
Section: Resultsmentioning
confidence: 99%
“…This case is also found in Hasanah, et.al (2022), which explains that some students were busy to scrolling social media and playing games when teacher was explain the material. The misuse of gadgets was also conveyed by Mauladina and Giantara (2020), in their research students more often use gadgets to access social media and game online during COVID-19 pandemic. Using gadgets for intensely will cause a dependence effects, and also can affected on student's psychology (Fitriana, 2020).…”
Section: ) For Studentmentioning
confidence: 96%
“…Gadget merupakan sebuah alat komunikasi yang paling popular dan banyak digunakan di era abad 21. Menurut pengertian gadget adalah perangkat elektronik kecil yang digunakan untuk komunikasi di era modern (Mauladina & Giantara, 2020;Pebriana, 2017). Tidak bisa dipungkiri bahwa banyak kemudahan yang diberikan oleh gadget, dibalik kemudahan yang diberikan juga terdapat dampak negatif berupa kecanduan pada penggunanya.…”
Section: Pendahuluanunclassified